2012
DOI: 10.1116/1.4737618
|View full text |Cite
|
Sign up to set email alerts
|

La2O3 gate insulators prepared by atomic layer deposition: Optimal growth conditions and MgO/La2O3 stacks for improved metal-oxide-semiconductor characteristics

Abstract: The authors investigated the optimal growth conditions for atomic layer deposition of La2O3 using tris(iso-propylcyclopentadienyl) lanthanum, La(iPrCp)3, and H2O, and identified two necessary conditions for achieving self-limiting growth: A low growth temperature (Ts) of 150 °C–175 °C and an extremely long purging after the H2O feed. Low Ts was also preferable for improving the electrical properties of the metal-oxide-semiconductor devices such as the dielectric constant (k), leakage current, and effective mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Moreover, as shown in Fig. 4 , varying degrees of humps in the C-V curves could be observed, which may be caused by the existence of interfacial traps [ 26 , 27 ]. Compared with Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, as shown in Fig. 4 , varying degrees of humps in the C-V curves could be observed, which may be caused by the existence of interfacial traps [ 26 , 27 ]. Compared with Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Besides, as the thickness of La 2 O 3 passivation layer increases, different degrees of frequency dispersion phenomenon at the weak inversion regions could be observed from the multi-frequency C-V curves in Figure 7, and the degrees of frequency dispersion phenomenon show a similar variation tendency with the anomalous humps in the C-V curves measured at 100 kHz. It has been reported that the existence of slow interface traps ( Q it ) should be responsible for the anomalous phenomenon at the weak inversion regions of C-V curves [26,27]. Considering this, the interface state density ( D it ) values of S1~S4 are discussed using the following relation of single-frequency approximation method through the forward swept C-V and G-V curves [28]:Dit=2qAGmaxω[(GmaxωCox)2+(1CmaxCox)2] where q is the elementary charge (1.602 × 10 −19 C), A is the area of the top electrode, C ox is the gate oxide capacitance as defined in Equation (1), G max is the peak value of G-V curve, and C max is the capacitance corresponding to G max at the same gate applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Another is that deposition processes for La 2 O 3 have been problematic. Numerous studies of atomic layer deposition (ALD) of La 2 O 3 can be found in the literature, and to date, La cyclopentadienyls (Cp), [10][11][12][13][14][15][16][17][18][19] P-diketonates, 9 silylamides, 20 amidinates, 21,22 and formidinates 23 have all been examined along with H 2 O, 10,13,[15][16][17][18][19][20][21][22][23] O 3 , 9,14 and O 2 plasmas 12,17 for oxidation. Despite this work, there has been limited success in developing a chemistry that can provide high-purity La 2 O 3 by self-limiting reactions as desired for ALD.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other work, in contrast, found that only low-temperature deposition (< 200 °C) resulted in self-limiting growth. 11,13 For Cp-type La compounds, the chemical insights obtainable from studying the effect of process variables on the growth of films appears to be limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation